Avaliação da produção de biogás obtido a partir de dejeto bovino e casca de café - Ferrari Fumian, Verônica Aparecida; da Silva Picanço, Tayná; Fonseca Porto, Luís Paulo; Bandoli Gomes, Camila de Paula; Ferrarez, Adriano Henrique (Latin American Journal of Energy Research, 2021)
Cattle and coffee farming have a significant share in the Brazilian Gross Domestic Product (GDP). These activities, however, produce large amounts of waste that cause significant environmental impacts. Anaerobic digestion presents itself as a solution in the management of this waste, resulting in the production of biogas and biofertilizer. This work’s objective was to evaluate the production and methane content (CH4) of the biogas obtained from bovine manure and coffee husk. Used two benchtop digesters triplicates: (i) D1 - bovine manure (1 Liter); and (ii) D2 - bovine manure and coffee husk (1 Liter: 1 Liter). Performed measurements of the volume and methane content (CH4) of the biogas produced weekly. They measured the pH of the remaining material in each anaerobic digester at the end of the experiment. The D2 triplicate showed accumulated biogas production with average CH4 contents higher than the D1 triplicate. The pH was in the optimum range for the anaerobic process in all digesters.